Pengaruh Edukasi PHBS Tentang Pengelolaan Sampah Dan Sanitasi Terhadap Pengetahuan Siswa SMP Nur Adia - Meutia Nanda; Muhammad Arif Ikhsan; Widya Fadhillah; Ira Sulastri Pasaribu; Qory Adinda Siregar (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Clean and Healthy Living Behavior (PHBS) is an important effort to improve students’ health through the implementation of healthy lifestyle habits, including waste management and environmental sanitation in schools. Poor school environmental conditions and inadequate sanitation can increase the risk of various diseases and affect students’ health behavior. This study aimed to analyze the effect of PHBS education regarding waste management and sanitation on the knowledge of students at SMP Nur Adia Tanjung Selamat, Deli Serdang Regency. This research used a quantitative method with a one-group pretest-posttest design involving 40 students from classes VII A and VII B selected using the total sampling technique. Data were collected through questionnaires administered before and after the educational intervention and analyzed using the Paired Sample t-test. The results showed that the average student knowledge score increased from 81.18 before the education to 86.58 after the education, with a p-value < 0.001, indicating a significant effect of the educational intervention on improving students’ knowledge..